Assessment and Evaluation of Teachers’ Performance and Professional Development - Ammasi, James (Journal of Interdisciplinary Perspectives, 2024)
Teacher performance is critical for student academic success, yet many teachers still need additional support to develop their professional competencies fully. This study aimed to address this gap by developing a targeted professional development program for teachers designed to enhance teacher performance. Using a research and development (R&D) design, the study involved 352 teachers from three divisions in Ilocos Norte, selected through Slovin’s formula and stratified proportionate random sampling. Additionally, 21 teachers and 3 professional development program implementers participated in focus group discussions, while 8 experts validated the program’s content. Data were gathered using teacher performance rating forms, interview guides, and content validation instruments and were analyzed through mean scores and thematic analysis. Findings revealed that while teachers generally perform satisfactorily according to professional standards, there is still room for growth. Teachers expressed that participating in more research-based and needs-driven professional development programs would help them further enhance their skills. Based on these findings, experts developed and validated a program as highly suitable for implementation. It is recommended that the program be adopted widely to improve teacher performance and support continuous professional growth.